„Substitute Relationship”: Significance in the Interpersonal Relationship of Caregivers and Children in Children's Homes (Training and Practice : Journal of Educational Sciences, 2012)
The practical aspects of the relationships developing between caregivers and youth temporarily residing in a children’s home within the Hungarian child protective institutional system are presented in this article. We will describe the Hungarian child protective interventions and establish the complementary conditions of socialization pertinent in children's homes. We will review the relevant of pedagogical and psycho-pedagogical research and will describe a new theory: „substitute relationship”.The concept of „substitute relationship” will help us describe the most important characteristics of the relationships between caregivers and children temporarily living in a residential institution, and provide ideas for further research.